An Overview of the Security Landscape of Virtual Mobile Networks - Ijaz Ahmad; Jarno Pinola; Ilkka Harjula; Jani Suomalainen; Erkki Harjula; Jyrki Huusko; Tanesh Kumar (IEEE Access)
5G enables the use of different types of services over the same physical infrastructure through the concepts and technologies of virtualization, softwarization, network slicing and cloud computing. Mobile Virtual Network Operators (MVNOs), using these concepts, provide an opportunity to share the same physical infrastructure among multiple operators. Each MVNO can have own distinct operating and support systems. However, the technologies used to enable such an environment have their own explicit security challenges and solutions. The integrated environment built upon these novel concepts and technologies, thus, will have complex security implications and requirements to be satisfied. In this vain, this article provides an overview of the security challenges and potential solutions for MVNOs.